Building construction illustrated - Ching, Francis D. K., 1943- (Hoboken, New Jersey : Wiley, 2014)
"This new edition provides the latest information in Ching's signature style. Its rich and comprehensive approach clearly presents all of the basic concepts underlying building construction. New to this edition are digital enhancements delivered as an online companion to the print edition and also embedded in e-book editions. Features include a 3D model showing how building components come together in a final project."--
-- The building site -- The building -- Foundation systems -- Floor systems -- Wall systems -- Roof systems -- Moisture and thermal protection -- Doors and windows -- Special construction -- Finish work -- Mechanical and electrical systems -- Notes on materials.
Includes bibliographical references and index.
Keywords: Building; House construction